Buckling Behaviour of Clamped-Clamped Rectangular Thin Plates Composite Materials for a Zig-Zag Model (Journal of University of Babylon for Engineering Sciences, 2018)
This paper focused mainly on the behavior buckling for the rectangular laminated plates made from three types of composite materials of a zig-zag model such as E-glass fiber / polyester (GFRP), carbon fiber / polyester (CFRP) and hybrid fibers / polyester (HFRP), under static buckling load and at room temperature (25Co). All the effects of plate determinants on the buckling load were studied for one type of a boundary condition, which was fixed on both sides, is clamped-clamped and free-free in other sides. The buckling analysis of these plates has been studied numerically and experimentally with different aspect ratio and constant thickness ratio. The experimental part is including the manufacture of composite materials laminated plates of a zig-zag model and determine the mechanical properties such as modulus of elasticity, yield stress, ultimate tensile strength and Poisson's ratio by tensile test for three types of composite materials such as GFRP, CFRP, and HFRP. The experiments of shear stress test was used to determine whether the layers would be the plates is delaminate layers during buckling test or not into the three types of composite materials samples. Experiments were also used to find the critical buckling load and maximum buckling deflection for clamped-clamped rectangular laminated plates of three types of composite materials for a zig-zag model with the effect of aspect ratios under uniformly distributed static compression load.Numerical analysis of critical buckling load and maximum buckling deflection are calculated for three types of composite materials thin plates for a zig-zag model with the effect of aspect ratios under uniformly distributed static buckling load, the finite elements method was used in ANSYS program version (15.0).The main conclusion of this research is that the presence of zig-zag fibers in the plate can improve the mechanical properties and increase the critical buckling load.  The maximum percentage errors between the experimental and numerical results are 29.23%, 30.20%, and 46.71% at aspect ratio (a/b=1) for GFRP, CFRP, and HFRP, respectively. The maximum deflection value is increased when the aspect ratio is increased under constant thickness ratio; also, the maximum deflection in GFRP composite materials rectangular laminated plates is greater than that in CFRP and HFRP.A good agreement is achieved between the two experimental ways for determining the critical buckling load and maximum buckling deflection results, the maximum absolute percentage error rates are about 1% and 1.1%, respectively.